Social Action and Social Solidarity: Community Empowerment in the Digital Age - Willya Achmad (International Publisher (YAPENBI), 2022)
The COVID-19 pandemic has had a significant impact on all aspects of people's lives. Even so, the Indonesian people have proven resilience and empowerment in the face of the Covid-19 pandemic. The existence of the internet and digital media has encouraged the emergence of digital social action and digital social solidarity. Therefore, this study aims to determine social action and social solidarity within the scope of community empowerment in the digital era as it is today. This study uses a qualitative approach with a descriptive method. The results of the study show that the Covid-19 pandemic has led to social actions where Indonesian people work together, collaborate, and show solidarity in helping others. Where this social action and social solidarity, although it arises in the digital dimension, in fact this movement has produced great benefits in terms of empowering the affected community in terms of the social economy and culture, and is still surviving to this day.